Claims In Respect Of Part Of Land: Whether Capable Of Being Protected By Caveats - Khaw, Lake Tee (Journal of Malaysian and Comparative Law, 1986)
Under the National Land Code 1965, a caveat maybe entered by the Registrar, at the instance of any person or body having a caveatable interest in the land, on the register document of title to any land. Such caveat will, depending on the intention of the caveator, bind either the land itself or a particular interest therein.